Does Cytoglobin Play a Role as Anti-Fibrosis? - Maftuhatun Fista Amalia; Sri Widia A. Jusman (Konsorsium Ilmu Biomedik Indonesia (KIBI), 2022)
Cytoglobin (Cygb) is a vertebrate globin protein that is synthesized by fibroblasts and expressed in a variety of organs. Cygb’s function is not fully understood. In contrast, activated fibroblasts (myofibroblasts) are known to produce collagen, which is the major component of the extracellular matrix (ECM) and contributes to abnormal wound healing. There are three phases in wound healing: (1) injury; (2) inflammation; and (3) tissue regeneration. Myofibroblasts will apoptosis throughout the healing phase. If myofibroblasts fail to undergo apoptosis, this might end in fibrosis. This condition induces relative hypoxia in fibrosis. Several investigations have found that overexpression of Cygb serves as an antifibrosis agent by reducing collagen production. The potential involvement of Cygb in avoiding fibrosis in diverse tissues is discussed in this article. Keywords: Cytoglobin (Cygb), wound healing, anti-fibrosis, collagen